Factors contributing to helminth prevalence after repeated mass administration of medicines in Anambra State, Nigeria - Ogechukwu B. Aribodor; Christopher Okaka; Sammy Sam-Wobo; Annick Bikoumou; Emmanuel Obikwelu (Scientific Reports)
Abstract Over the past decade, Mass Administration of Medicines (MAM) has been a key strategy for controlling schistosomiasis and soil-transmitted helminthiasis (STHs) in Anambra State, Nigeria. This longitudinal study, conducted from 2017 to 2019, evaluated the impact of interventions for controlling schistosomiasis (SCH) and STHs in recipient communities. A total of 1,046 pupils aged 5 to 16 years were enrolled, with Kato-Katz and urine filtration methods used for faecal and urine sample analysis. A structured questionnaire was administered to 243 people to assess the contextual factors. At baseline, prevalence was 8% (82/1046), with A. lumbricoides (7.0%), T. trichiura (1.0%), Hookworm (0.1%), and S. haematobium (0.5%) observed. Co-infection was 1%. At follow-up, prevalence decreased to 6% (65/1046), with A. lumbricoides (2.0%), T. trichiura (2.2%), and S. haematobium (2%) observed, and co-infection was 0.2%. Infection levels varied by location (p > 0.05), with socio-economic status and inadequate WASH (Water, Sanitation, and Hygiene) infrastructure contributing to transmission risk. Most respondents (87%) earned less than $50 per month, and 39% practiced open defecation. The persistence of open defecation highlights critical gaps in WASH that undermine sustainable Neglected Tropical Diseases (NTD) control. Addressing cultural and economic challenges, alongside improving WASH infrastructure, is essential to sustain MAM’s impact.